Microglia and Wnt Pathways: Prospects for Inflammation in Alzheimer’s Disease - Yang, Yunying; Zhang, Zhentao (Frontiers in Aging Neuroscience, 2020)
Alzheimer’s disease (AD) has been a major health issue for more than one century since it was first reported in 1906. As one of the most common neurodegenerative diseases, AD is characterized by the presence of senile plaques and neurofibrillary tangles (NFTs) in the affected brain area. Microglia are the major regulator of neuroinflammation in the brain, and neuroinflammation has been the core pathophysiological process of various neurodegenerative diseases. In the central nervous system (CNS), microglia play a dual role in AD development. For one thing, they degrade amyloid β (Aβ) to resist its deposition; for another, microglia release pro-inflammatory and inflammatory factors, contribute to neuroinflammation as well as the spreading of Aβ and tau pathology. Wnt pathways are important regulators of cell fate and cell activities. The dysregulation of Wnt pathways is responsible for both abnormal tau phosphorylation and synaptic loss in AD. Recent studies have also confirmed the regulatory effect of Wnt signaling on microglial inflammation. Thus, microglia, Wnt pathways and their possible interactions may open up a new direction for underlying the mechanisms of neuroinflammation in AD. In this review, we summarize the function of microglia, Wnt pathways, as well as their roles in AD in order to provide new ideas for understanding the pathogenesis of AD.